Development of Capacitive-Type Sensors by Electrochemical Anodization: Humidity and Touch Sensing Applications - Joaquim O. Carneiro (MDPI AG, 2021)
This work describes the development of a capacitive-type sensor created from nanoporous anodic aluminium oxide (NP-AAO) prepared by the one-step anodization method conducted in potentiostatic mode and performed in a low-cost homemade system. A series of samples were prepared via an anodization campaign carried out on different acid electrolytes, in which the anodization parameters were adjusted to investigate the effect of pore size and porosity on the capacitive sensing performance. Two sensor test cases are investigated. The first case explores the use of highly uniform NP-AAO structures for humidity sensing applications while the second analyses the use of NP-AAO as a capacitive touch sensor for biological applications, namely, to detect the presence of small “objects” such as bacterial colonies of Escherichia Coli. A mathematical model based on equivalent electrical circuits was developed to evaluate the effect of humidity condensation (inside the pores) on the sensor capacitance and also to estimate the capacitance change of the sensor due to pore blocking by the presence of a certain number of bacterial microorganisms. Regarding the humidity sensing test cases, it was found that the sensitivity of the sensor fabricated in a phosphoric acid solution reaches up to 39 (pF/RH%), which is almost three times higher than the sensor fabricated in oxalic acid and about eight times higher than the sensor fabricated in sulfuric acid. Its improved sensitivity is explained in terms of the pore size effect on the mean free path and the loss of Brownian energy of the water vapour molecules. Concerning the touch sensing test case, it is demonstrated that the NP-AAO structures can be used as capacitive touch sensors because the magnitude of the capacitance change directly depends on the number of bacteria that cover the nanopores; the fraction of the electrode area activated by bacterial pore blocking is about 4.4% and 30.2% for B1 (E. Coli OD600nm = 0.1) and B2 (E. Coli OD600nm = 1) sensors, respectively.